DETERMINANTS OF GENERATION Z WEST JAVA'S INTENTION TO ENDOW WAQF IN THE WAQF FOREST SECTOR: A THEORY OF REASONED ACTION (TRA) APPROACH - Aulia, Rifka (Cahaya Ilmu Bangsa, 2025)
Indonesia has the second highest deforestation rate in the world, causing many environmental problems. In addition, green waqf as an instrument of Islamic philanthropy has the concept of waqf forest, which is a forest utilization that cannot be converted. In addition, Indonesia has a huge waqf potential, but the collection is still very small. This study aims to identify the factors that influence West Java Generation Z's intention to donate to the waqf forest sector using the Theory of Reasoned Action (TRA) approach. The object of this research is generation Z in West Java who have never donated waqf in the waqf forest sector. This research method uses a quantitative method with a descriptive approach. The result is the interest of generation Z in Java Island in making waqf in the waqf forest sector is still relatively low, although the figures obtained almost touch the figures with a moderate category, but the figures are still far from expectations. Thus, strategic steps can be developed to maximize the collection of waqf through money in the waqf forest sector in maintaining the existence of forests as the lungs of the world while contributing to realizing the Sustainable Development Goals (SGDs), especially on point 13, climate change; and point 15, life on land.